2012
DOI: 10.1063/1.4733388
|View full text |Cite
|
Sign up to set email alerts
|

Towards spin injection from silicon into topological insulators: Schottky barrier between Si and Bi2Se3

Abstract: A scheme is proposed to electrically measure the spin-momentum coupling in the topological insulator surface state by injection of spin polarized electrons from silicon. As a first approach, devices were fabricated consisting of thin (<100nm) exfoliated crystals of Bi 2 Se 3 on n-type silicon with independent electrical contacts to silicon and Bi 2 Se 3 . Analysis of the temperature dependence of thermionic emission in reverse bias indicates a barrier height of 0.34 eV at the Si-Bi 2 Se 3 interface. This robus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 28 publications
(32 reference statements)
0
35
0
Order By: Relevance
“…This is because the spin-momentum locking makes the charge and spin scattering times to be the same, and therefore the spin diffusion length is equal to the electron mean free path in the TI surface state. 219) In such a situation, the spin polarization is significantly diminished in a diffusive transport (to the order of Ák=k F , where Ák is the shift of the Fermi surface induced by the applied electric field), 220) and the experiment must be done in a ballistic transport regime to detect a spinpolarized current. 221) No such experiment has been reported for 3D TIs, but in the CdTe/HgTe/CdTe quantum well in the 2D TI regime, spin polarization of the edge current has been confirmed, 70) thanks to the long electron mean free path achievable in HgTe quantum wells.…”
Section: Surface State and Helical Spin Polarizationmentioning
confidence: 99%
“…This is because the spin-momentum locking makes the charge and spin scattering times to be the same, and therefore the spin diffusion length is equal to the electron mean free path in the TI surface state. 219) In such a situation, the spin polarization is significantly diminished in a diffusive transport (to the order of Ák=k F , where Ák is the shift of the Fermi surface induced by the applied electric field), 220) and the experiment must be done in a ballistic transport regime to detect a spinpolarized current. 221) No such experiment has been reported for 3D TIs, but in the CdTe/HgTe/CdTe quantum well in the 2D TI regime, spin polarization of the edge current has been confirmed, 70) thanks to the long electron mean free path achievable in HgTe quantum wells.…”
Section: Surface State and Helical Spin Polarizationmentioning
confidence: 99%
“…Besides, Bi 2 Te 3 and Bi 2 Se 3 are all stoichiometric rhombohedral materials with quintuple stacked layered structure and relatively weak layer-tolayer van der Waals coupling, [19] as shown in Figure 1a. More importantly, it was suggested that the construction of Bi 2 Se 3 on Si could introduce a very high Schottky barrier of ≈0.34 eV at the interface, [22,28,29] which can be used to accelerate the separation of photo-excited carriers in Si or Bi 2 Se 3 and inhibit their recombination simultaneously, thus the outstanding photoelectric responses were usually obtained. More importantly, it was suggested that the construction of Bi 2 Se 3 on Si could introduce a very high Schottky barrier of ≈0.34 eV at the interface, [22,28,29] which can be used to accelerate the separation of photo-excited carriers in Si or Bi 2 Se 3 and inhibit their recombination simultaneously, thus the outstanding photoelectric responses were usually obtained.…”
mentioning
confidence: 99%
“…51 We have used the condition V≫E in the above approximation, which is reasonable for the Ag/Bi 2 Se 3 junctions. As the TI SOC causes the Rashba-type splitting by affecting the tunneling part of the metallic QWS, the spin gap ΔE defined in Figure 2a should be proportional to the tunneling amplitude in TI:…”
Section: Resultsmentioning
confidence: 99%